Repurposing without purpose? Early innovation responses to the COVID‐19 crisis: Evidence from clinical trials. (18th February 2021) - Hanisch, Marvin; Rake, Bastian
Abstract : The novel coronavirus has created one of the biggest social and economic challenges in recent decades. Since a critical issue in overcoming a large‐scale pandemic involves finding effective treatments for the disease, there is typically urgent pressure on the health‐care sector to develop innovations to combat the pandemic. Recently, scholars have argued that repurposing – that is, reusing an existing innovation in a different context – allows for such rapid innovation responses and can reduce costs, as the groundwork has already been laid. In this paper, we compare these benefits with the considerable disadvantages associated with innovation repurposing, including lowered barriers to entry, which can lead to declining average quality and duplicate work. Using data on 2, 456 COVID‐19‐related clinical trials initiated between December 2019 and July 2020, we find that merely one‐third of the trials actually investigated drugs or vaccines, whereas the rest focused on diagnostics and crisis management issues. In the trials concerning drug testing, we find that drug repurposing is a predominant innovation strategy, but many trials tested the same (combination of) drugs. This indicates an inefficient use of resources and reductions in the average variety and novelty of clinical trials. Furthermore, the small percentage of biopharmaceutical firms involved in the search for COVID‐19 treatments raises the question of whether firms may have insufficient incentives to redirect innovation efforts to respond to the pandemic. Our paper contributes to crisis management research, the nascent debate on COVID‐19, and the emerging literature on innovation repurposing.